Aktivitas Sitotoksik Ekstrak Heksan, Ekstrak Etil Asetat, Ekstrak Etanol Buah Mengkudu (Morinda citrifolia L ) Terhadap Sel T47D - Maryati Maryati; Ahmad Novian Nur Anas; Muhammad Nur Khairudin (Pharmacon: Jurnal Farmasi Indonesia, 2020)
Noni fruit (Morinda citrifolia L) is one of the natural ingredients commonly used as traditional medicine to overcome various diseases, such as cancer. Noni fruit contains anthraquinone and coumarin which have anticancer effects. This study aims to determine the cytotoxic effects of n-hexane, ethyl acetate and ethanol extract of noni fruit and to determine the presence of anthraquinone and coumarin in the extract. Extraction was carried out by maceration method using n-hexane, followed by ethyl acetate and ethanol. The cytotoxic activity on T47D cells was carried out by the MTT method. The presence of anthraquinone and coumarin was identified using thin layer chromatography (TLC). Results showed that n-hexane extract had moderate cytotoxic effect on T47D cells with IC50 value of 582.13 ± 61.64 µg/mL, while the ethanol and ethyl acetate extract did not have cytotoxic effect on T47D cells. TLC results indicated that n-hexane extract of noni fruit contains anthraquinone and coumarin.